faktor-faktor yang mempengaruhi kejadian postpartum blues di BPM Elizabet wilayah kerja puskesmas payung sekaki - Anjeli indah Purwati; Nurhidaya Fitria; Wira Ekdeni Aifa (HEALTH CARE: JURNAL KESEHATAN, 2023)
Postpartum blues, also known as postpartum depression, is a phenomenon of psychological changes experienced by postpartum mothers. Postpartum blues occurs on day three to day five and within 14 days. Factors that cause Postpartum blues are age, occupation, family support, income. The purpose of this study was to determine the relationship between age, occupation, family support, and income with the incidence of Postpartum blues. This research type is a quantitative research with observational-analytic method using cross-sectional research design. Sampling was performed using random sampling technique. Collected data using the Edinburgh Postnatal Depression Scale (EPDS) questionnaire and the Postpartum Depression Predictors Inventorr (PDPI). Analyzed data using Chi Square with a total of 33 respondents. The results obtained showed a significant relationship in all variables with the incidence of Postpartum Blues. Age variables, family support, income with a p-value of 0.000 and work variables with a p-value of 0.001 which means there is a relationship between variables on the incidence of Postpartum Blues. It is recommended for midwives to improve health services to provide supporting facilities such as postpartum counseling, postpartum hazards, and abnormalities that occur during the postpartum period to reduce the incidence of Postpartum Blues.